Efeito do tratamento térmico na relaxação magnética de microfios amorfos de CoFeSiB recobertos por vidro - Chrischon, Dieivase da Silva (2012)
Magnetoimpedance has been proved to be an excellent tool to study the magnetization dynamics and the ferromagnetic resonance (FMR) linewidth provides a convenient way for measuring damping parameters in magnetic materials. The FMR linewidth depends on intrinsic magnetic damping and additional magnetic inhomogeneities, but complete understanding of the origin of these damping parameters is still unaccomplished. Besides the fundamental physics interest, the study of damping term and magnetization dynamics is very important for the development of any device which has its physical effect associated with the reversal of magnetization. Furthermore, the FMR linewidth is a very sensitive way to study the structural quality of magnetic samples, in both bulk and thin film geometries. In this work the magnetic relaxation of CoFeSiB glass-covered microwire was investigated by ferromagnetic resonance (FMR) linewidth measurements. We have identified the main damping mechanisms and quantified these damping terms, showing the effect of annealing temperature to them. The study have shown that there are three main damping mechanisms responsible for the FMR linewidth, the Gilbert damping parameter, a damping mechanism due to anisotropy dispersions and two-magnon scattering. The Gilbert damping parameter is almost constant and not influenced by the annealing. The FMR linewidth is very sensitive to anisotropy dispersions and this mechanism has a great contribution to the magnetic relaxation. The two-magnon scattering is an assignment of the inhomogeneities present in the samples and its contribution to the FMR linewidth decrease with the annealing temperature until a critical value, as a result of a decrease of inhomogeneities due to a reduction of the internal stress level. A further increase in the annealing temperature produces an increase in the two-magnon scattering contribution which is an indication of the growing of nanocrystals acting as scattering centers to the spin waves.